Medical Cannabis in Pediatric Oncology: Friend or Foe? - Megan Malach; Igor Kovalchuk; Olga Kovalchuk (MDPI AG, 2022)
The antineoplastic effects of cannabis have been known since 1975. Since the identification of the components of the endogenous cannabinoid system (ECS) in the 1990s, research into the potential of cannabinoids as medicine has exploded, including in anti-cancer research. However, nearly all of this research has been on adults. Physicians and governing bodies remain cautious in recommending the use of cannabis in children, since the ECS develops early in life and data about cannabis exposure in utero show negative outcomes. However, there exist many published cases of use of cannabis in children to treat pediatric epilepsy and chemotherapy-induced nausea and vomiting (CINV) that show both the safety and efficacy of cannabis in pediatric populations. Additionally, promising preclinical evidence showing that cannabis has anti-cancer effects on pediatric cancer warrants further investigation of cannabis' use in pediatric cancer patients, as well as other populations of pediatric patients. This review aims to examine the evidence regarding the potential clinical utility of cannabis as an anti-cancer treatment in children by summarizing what is currently known about uses of medical cannabis in children, particularly regarding its anti-cancer potential.